Metal Music as a Medium of Da'wah Communication (Album “7:172” Band Purgatory) - Sabian Ray Dhista Almayda*; Rahmawati Zulfiningrum (Universitas Syiah Kuala, 2023)
Purgatory is a metal band from Jakarta that creates Music that contains a Message of da'wah in it. Purgatory released an album entitled